Adaptation and Validation of the Learning Style Inventory Version 3.1 in Greek Language: A Methodological Study - Andreou, Christos; Lemonidou, Chryssoula; Mattheou, Kyriacos; Merkouris, Anastasios; Papastavrou, Evridiki (My University, 2015)
Abstract BACKGROUND AND PURPOSE: The nursing research on learning differences is currently expanding, suggesting the need for trustful measurements. This study aimed to adapt and cross-culturally validate the Learning Style Inventory. METHODS: The first phase involved symmetrical translation and adaptation to the Greek target language. The second phase concerned the psychometric testing. RESULTS: Internal reliability showed satisfactory alpha values. Kappa coefficients supported the test-retest reliability, and paired t test correlations justified the stability. Factor analysis yielded 2 constructs fitted with theory. The internal validity was also evidenced. The nursing students' learning style profile was discussed within their educational field and cultural background. CONCLUSIONS: The inventory presented content and construct equivalence to original scales. Certain implications were drawn for nursing supporting the utility of learning styles' measurements.